Thermoelectric transport at F4TCNQ–silicon interface - Naiming Liu; Jonathan Peters; Ashok Ramu; Jerrold A. Floro; John E. Bowers; Mona Zebarjadi (APL Materials, 2019)
Hybrid organic-inorganic materials are among the latest class of materials proposed for thermoelectric applications. The organic-inorganic interface is critical in determining the effective transport properties of the hybrid material. We study the thermoelectric properties of the tetrafluoro-tetracyanoquinodimethane (F4TCNQ)–silicon interface. Transfer of electrons from silicon to F4TCNQ results in holes trapped within the screening length of the interface that can move parallel to the interface. We measure the response of these trapped charges to applied temperature differential and compare the thermoelectric transport properties of the silicon with and without F4TCNQ. The results confirm the presence of interface charges and demonstrate an enhanced interface thermoelectric power factor. These outcomes of this study could be used in designing 3D hybrid structures with closely packed interfaces to replicate a bulk thermoelectric material.